Brain Complete Response to Cabozantinib prior to Radiation Therapy in Metastatic Renal Cell Carcinoma. (13th February 2019) - Uche, An; Sila, Chad; Tanoura, Tad; Yeh, James; Bhowmick, Neil; Posadas, Edwin; Figlin, Robert; Gong, Jun
Abstract : Cabozantinib represents an established vascular endothelial growth factor- (VEGF-) tyrosine kinase inhibitor (TKI) in the treatment paradigm of metastatic renal cell carcinoma (mRCC). Its activity in mRCC patients with brain metastases (BMs) has been largely underreported in prospective clinical trials. We present the unique case of a heavily pretreated mRCC patient with BMs who achieved a brain complete response to cabozantinib prior to receiving radiation therapy. We end with a literature review and discussion of the biologic rationale and growing evidence supporting the intracranial activity of cabozantinib.